The Prevalence of Hypertension in the Population without Awareness of the Disease: Data from a Rural Town of Shandong Province, China - Maoti Wei; Li Dong; Fenghua Wang; Kai Cui; Jiamin Yu; Delong Ma; Ning Yang; Yuming Li (International Journal of Hypertension)
Objective. To understand the prevalence of hypertension in the population without awareness of hypertension in a rural area, a cross-sectional study was carried out. Methods. Blood pressures were measured in residents over 60 years during the National Basic Public Health Service project carrying on in a rural town of Shandong province. Combined with detail information of the hypertension disease history, the status of prevalence of hypertension was calculated. Basic information and clinical laboratory examinations were analyzed with Student’ t or t’ or chi-square test for univariate analysis. Multinomial logistic analysis was used in exploring multiple variables. Results. According to the individual history and blood pressure levels, the awareness rate of hypertension in the population over 60 years old was 50.3% (1285/2554, 95% CI: 48.3–52.3%). The prevalence of hypertension was 55.1% (1270/2304, 95% CI: 53.1–57.2%) in the population without awareness of hypertension, in which the proportion of stage 1 hypertension was 58.8% (747/1270), stage 2 hypertension was 28.9% (367/1270), and stage 3 hypertension was 12.3% (156/1270). The prevalence of hypertension in men was 54.4% (611/1124, 95% CI: 51.4–57.3%), which was almost the same as that in women (55.8%, 659/1180, 95% CI: 53.0–58.7%) (X2 = 0.515, P=0.473). The prevalence of hypertension increased with age (X2trend = 11.848, P=0.001). Age, BMI, total cholesterol, triglyceride, and drinking rate were positively correlated with the prevalence of hypertension, that is, the higher the level of these factors, the higher the prevalence of hypertension; on the contrary, LDL and smoking rate might be negatively correlated with the prevalence of hypertension, which means, the higher the prevalence of hypertension, the lower the level of these two indicators. Binary and multinominal logistic results showed that age, BMI, and drinking had stronger effects on the higher blood pressure level. Conclusions. The awareness rate of hypertension among the elderly in a rural area needs to be further improved. In the prevention and control of hypertension, close attention should be paid to the group of elder, high BMI index, high levels of total cholesterol and triglyceride, and drinking habits.